Design of wireless device to measure plantar pressure and gait analysis - Khatri, Mahendra; Dabadi, Sambardhan; Shrestha, Sandeep Kumar; Acharya, Saugat; Tamang, Sudip; Shakya, Swornima (Journal of Innovations in Engineering Education, 2019)
Foot plantar pressure is the pressure field that acts between the plantar region of the foot and supporting ground. The pressure exerted on the variable region of the foot can be determined using discrete pressure sensors. Information obtained from these sensors is useful in the measurement of gait and posture for diagnosing various problems associated with a lower limb, footwear design, and sports biomechanics.This project is aimed to design a portable in-shoe plantar pressure and gyroscope-based gait angle measurement system. Six Force Sensitive Resistor (FSR) placed in the sole (hallux, 1st, 5th metatarsal, midfoot lateral, midfoot medial and heel respectively) detects the plantar pressure and gyroscope placed at the ankle, knee and hip help measure the orientation and angle of joint movement during various phases of gait. The study among 16 male and 16 female subjects illustrated the significant pressure variation (p